Predictive Factors of Cerebral Aneurysm Rerupture After Clipping - Chang, Yu-Jun; Liu, Chi-Kuang; Cheng, Chun-Yuan; Shih, Yu-Cheng; Wang, Shih-Chun; Lin, Chung-Chih; Lin, Chih-Ming (Frontiers in Neurology, 2022)
Background: Cerebral aneurysms pose an imminent threat and can cause fatality. Due to its subtle and nonspecific initial presentations, cranial aneurysms are often neglected during both daily neurological and physical examinations. We attempt to look for important factors for early prediction of long-term outcomes post aneurysmal clipping surgery. Methods: This retrospective study included 171 patients with cerebral aneurysm who had completed aneurysmal clipping treatment and collected their demographic data and medical records. The outcome assessments include neuroimaging records, Hunter and Hess scale, and modified Rankine scale (mRS) during hospitalization and follow-up after discharge. Results: After aneurysmal clipping treatment, 83 patients (48.5%) had subsequent ruptured aneurysms. The scores of the ruptured group on the Hunt & Hess scale and mRS were significantly higher than those of the unruptured group. Multiple Cox proportional-hazards regression also showed that postoperative mRS > 2, smoking, and two or more aneurysms were potentially important risk factors leading to aneurysm rupture (the corresponding hazard ratio were 5.209, 2.109, and 2.775, respectively) in patients. In addition, the location of an aneurysm on the anterior cerebral artery (ACA) or the posterior communicating (Pcom) artery had a higher risk of rupture (the corresponding hazard ratio were 1.996 and 2.934, respectively). Conclusions: Compared with the Hunter and Hess scales, the mRS scale does not have inferior predicting power. Smoking and multiple aneurysms are potentially risk factors for aneurysm rupture. Most aneurysms are located along the ICA, but aneurysms located at the ACA or Pcom site are most likely to rupture.